Surface Enhanced Raman Scattering (SERS) for the Detection of Oxidative Stress Markers Using Si Nanowires (SiNWs)/Ag Nanostructures Fabricated by Metal Assisted Chemical Etching (MACE) - Ioannis Kochylas; Anastasia Kanioura; Georgia Geka; Vlassios Likodimos; Spiros Gardelis; Anastasios Dimitriou; Nikolaos Papanikolaou; Sotirios Kakabakos; Panagiota Petrou (Proceedings)
In this work, silicon nanowires were constructed by metal-assisted chemical etching and decorated with silver nanoparticles and used as substrates for the SERS determination of oxidative stress markers, namely glutathione, malondialdehyde and catalase. The assays were sensitive, with detection limits of 50 and 3.2 nM for glutathione and malondialdehyde, respectively, and 0.5 μg/mL for catalase, indicating the capability of the proposed substrates to be implemented for the determination of various oxidative stress markers.